COMMUNICATION STRATEGY OF DAKWAH IN COMMUNITY OF THE MODERN ERA (CASE STUDY IN LENGKONG VILLAGE, SUKOREJO DISTRICT, PONOROGO REGENCY) - Millah, Zaimatul (QAULAN: Journal of Islamic Communication, 2021)
Voicing goodness including preaching is an obligation for Muslims. In contrast to the method of preaching the Prophet Muhammad in the past, the ease of doing anything now cannot be separated because of the role of technological developments in disseminating information including preaching. The modern era provides an opportunity for us to invite us to do good by preaching by utilizing technology. However, the ease of access now is also inseparable from the communication strategy of preaching da'i in packaging da'wah messages to attractive and light da'wah methods which are also very much needed by modern society. In this paper the author presents empirical data from the preaching of the Prophet Muhammad which is still relevant to be implemented in the communication strategy of da'wah in modern society. The purpose of this research is that the modern era da'wah strategy must be able to be side by side with advanced science and technology. So that the use of technology in preaching is needed in order to increase faith and devotion to Allah through verbal communication (bil al-oral) and nonverbal (bil al hal). The result of this research is that modern society in Lengkong Village gives a good response and can apply what has been conveyed through the da'wah communication strategy carried out, by utilizing the sophistication of today's technology. Keywords: Strategy, Da'wah Communication, Society, Modern Era